A finite element method based comparative fracture assessment of carbon black and silica filled elastomers: Reinforcing efficacy of carbonaceous fillers in flexible composites. (November 2020) - Goswami, Mohit; Ghosh, Moni Mahesh; Dalmiya, Mahawat Singh; Sharma, Sujit; Ghorai, Sanjoy Kumar; Chattopadhyay, Santanu
Abstract: This study is focused on numerical investigation on fracture behaviors of carbon black (CB) and silica filled elastomeric composites. Finite element analysis (FEA) in compliance with multi-specimen method is used to calculate J-integral and geometry factor of the rubber composites up to a displacement of 20 mm for single edge notch in tension (SENT) and double edge notch in tension (DENT) specimens. An empirical relationship between crack tip opening displacement (CTOD) and crack advancement is established depending on notch to width ratio ( NWR ). The stress contours across the notches for SENT and DENT specimens is discussed briefly. It is found that fracture propagation resistance of CB filled elastomer is 125% more than that of silica filled elastomer. Although, Silica filled elastomer have good tensile strength and crosslink density but it fails to replace carbon black in terms of fracture properties. The critical J-integral for CB filled elastomer is 18.7% and 32.2% more than silica filled elastomer for SENT and DENT specimens respectively. The effect of specimen type on various fracture properties is also explored. The factor of safety is found to be significantly more in case of CB filled elastomers making them less vulnerable to crack propagation and catastrophic failure. Graphical abstract: Image 1 Highlights: Non-linear fracture analysis of SENT and DENT geometries is performed. Factor of safety based mechanical characterization is performed. Stress contours across notches is presented. Reinforcing efficacy of CB filled hybrid elastomeric systems is discussed. FEA is used to characterize fracture of elastomeric composites.